2012
DOI: 10.1007/s00018-012-1215-y
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 depletion in a mouse model causes lethality, pigmentation deficits and reduction in protein synthesis efficiency

Abstract: The receptor for activated C-kinase 1 (RACK1) is a conserved structural protein of 40S ribosomes. Strikingly, deletion of RACK1 in yeast homolog Asc1 is not lethal. Mammalian RACK1 also interacts with many nonribosomal proteins, hinting at several extraribosomal functions. A knockout mouse for RACK1 has not previously been described. We produced the first RACK1 mutant mouse, in which both alleles of RACK1 gene are defective in RACK1 expression (ΔF/ΔF), in a pure C57 Black/6 background. In a sample of 287 pups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 64 publications
5
71
0
Order By: Relevance
“…In addition, we found that knockdown of RACK1 induced apoptosis. These results are consistent with earlier observations that deletion of the RACK1 gene is embryonically lethal (41). We believe that a certain level of cell death in RACK1 knockdown cells partially affected viral replication, which suggests that the apoptosis induced by RACK1 knockdown does not favor IBDV growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, we found that knockdown of RACK1 induced apoptosis. These results are consistent with earlier observations that deletion of the RACK1 gene is embryonically lethal (41). We believe that a certain level of cell death in RACK1 knockdown cells partially affected viral replication, which suggests that the apoptosis induced by RACK1 knockdown does not favor IBDV growth.…”
Section: Discussionsupporting
confidence: 93%
“…The conserved seven-blade propeller structure gives RACK1 a strong protein binding capacity. RACK1 is highly conserved in all species, such as human, mice, chicken, canine, and swine (41). It has been reported that RACK1 can interact with multiple proteins, such as Src (42), Hif-1 ␣ (43), androgen receptor (44), JAKs (45), and STATs (46), suggesting that RACK1 may act as a scaffolding protein, recruiting various proteins, providing a platform for protein interaction, and playing a critical role in different aspects of cell regulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…A recent hypomorphic model for RACK1 shows a pretty unique phenotype, characterized by reduced translation and a white bellyspot. 113 These data suggest that RACK1 affects the specific translation of mRNAs, as recently suggested by its binding to the b-actin mRNA/ZBP1 complex, 114 and its essential role in miRNA-regulated translation. 115,116 A powerful oncogenic pathway converging on translation is driven by Myc oncogene.…”
Section: The Case For Rapamycin-insensitive Translationsupporting
confidence: 58%
“…Deletion of RACK1 is embryonically lethal [69], whereas IQGAP1 knockout mice are viable [66], and clearly there may be challenges to achieving selective disruption of the RACK1-PP2A complex whilst avoiding interference with other RACK1 protein-protein interactions, at least in the case where a binding site on RACK1 is to be exploited. A key question, then, is whether it is feasible to block a scaffold protein such as RACK1 at a specific interaction point to gain a therapeutic benefit without disruption of its other functions.…”
Section: Discussionmentioning
confidence: 99%